Photographic self-fashioning. The role of photography in community-formation by the skagen painters - Mette Bøgh Jensen (Journal of Aesthetics & Culture)
This article looks at a selection of photos from the artists’ colony in Skagen Denmark and argues, that the photographic representations from the colony throughout the 20th century have played a minor role in the Danish art historiography on the subject. The article examines how the group identity and the community are depicted in a number of photographs from the 1870s and 1880s, and analyses how these photographs can be viewed as performative acts, which helped bolster the group identity and community-formation. The analysis thus emphasises the importance of the photographic act itself, arguing that the photographs not only function as witnesses to events that have taken place, but that they also convince the viewer of community formation. It is argued that the photographs of communal activities do not only represent a “pastness”, but that they also indicate a present and point to community formation. The empirical material consists of the artists’ accounts of being an artist in an artists’ colony such as anecdotes, letters, eyewitness accounts published in contemporary media and some of the photographs of the artists’ communal activities in the collection of Art Museums of Skagen.